SYMMETRY AS CONCEPTUAL METAPHOR IN WALKER’S THE COLOR PURPLE - Tapia, Elena (International Journal of English Studies, 2003)
The author analyzes three types of the conceptual metaphor of embodied symmetry in Alice Walker’s novel, The color purple (1982). These metaphorical projections, perceived as equilibrium and its breakage in abstract phenomena, enable readers to reexamine issues of race, non-traditional families, and gender roles. The dis/equilibrium emerges in the novel’s epistolary structure. Biological equilibrium breaks in incidents of rape and incest. Walker creates characters in the novel through default-concept opposites of black/white, submissive/dominant, male/female and others. These contraries foreground issues of race and gender. The novel’s asymmetries engage readers, leading them to rethink individual character histories and motives. The removal of objects (e.g., rape, mothers deprived of children) suggests conceptual asymmetry and alerts readers to parallel themes of sexual and racial oppression. Subjugation sometimes subtle, sometimes blatant- manifests in simple oppositions. In epistemological terms, readers seek causal explanations for the asymmetries of the narrative, interpreting each to recover its history.